'Enter at your own risk': a multimethod study of air quality and biological measures in Canadian waterpipe cafes. Issue 2 (25th October 2013) - Zhang, Bo; Haji, Farzana; Kaufman, Pamela; Muir, Sarah; Ferrence, Roberta
Abstract : Background: Tobacco and non-tobacco-based waterpipe smoking has increased exponentially in many countries in recent decades, particularly among youth and young adults. Although tobacco smoking is banned in many indoor public places, waterpipe smoking, ostensibly non-tobacco, continues in Ontario and other jurisdictions where only tobacco smoking is prohibited. This study assessed air quality and exposure in waterpipe cafes using multiple methods and markers. Methods: Indoor (n=12) and outdoor (n=5) air quality was assessed in Toronto, Canada waterpipe cafes from 30 August to 11 October 2012. Real-time measurements of air nicotine, fine particulate matter less than 2.5 microns in diameter (PM2.5 ) and ambient carbon monoxide (CO) were collected in 2 h sessions. Levels of CO in breath were collected in non-smoking field staff before entering and upon leaving venues. Observations of occupant behaviour, environmental changes and venue characteristics were also recorded. Results: In indoor venues, mean values were 1419 µg/m 3 for PM2.5, 17.7 ppm for ambient CO, and 3.3 µg/m 3 for air nicotine. Levels increased with increasing number of active waterpipes. On outdoor patios, mean values were 80.5 µg/m 3 for PM2.5, 0.5 ppm for ambient CO, and 0.6 µg/m 3 for air nicotine. Air quality levels in indoor waterpipe cafes are hazardous for human health. Outdoor waterpipe cafes showed less harmful particulate levels than indoors, but mean PM2.5 levels (80.5 µg/m 3 ) were still 'poor'. Conclusions: Staff and patrons of waterpipe cafes are exposed to air quality levels considered hazardous to human health. Results support eliminating waterpipe smoking in hospitality venues indoors and out.